Identification and characterization of Crr1a, a gene for resistance to clubroot disease (Plasmodiophora brassicae Woronin) in Brassica rapa L. - Katsunori Hatakeyama; Keita Suwabe; Rubens Norio Tomita; Takeyuki Kato; Tsukasa Nunome; Hiroyuki Fukuoka; Satoru Matsumoto (PLoS ONE, 2013)
Clubroot disease, caused by the obligate biotrophic protist Plasmodiophora brassicae Woronin, is one of the most economically important diseases of Brassica crops in the world. Although many clubroot resistance (CR) loci have been identified through genetic analysis and QTL mapping, the molecular mechanisms of defense responses against P. brassicae remain unknown. Fine mapping of the Crr1 locus, which was originally identified as a single locus, revealed that it comprises two gene loci, Crr1a and Crr1b. Here we report the map-based cloning and characterization of Crr1a, which confers resistance to clubroot in Brassica rapa. Crr1a(G004), cloned from the resistant line G004, encodes a Toll-Interleukin-1 receptor/nucleotide-binding site/leucine-rich repeat (TIR-NB-LRR) protein expressed in the stele and cortex of hypocotyl and roots, where secondary infection of the pathogen occurs, but not in root hairs, where primary infection occurs. Gain-of-function analysis proved that Crr1a(G004) alone conferred resistance to isolate Ano-01 in susceptible Arabidopsis and B. rapa. In comparison, the susceptible allele Crr1a(A9709) encodes a truncated NB-LRR protein, which lacked more than half of the TIR domain on account of the insertion of a solo-long terminal repeat (LTR) in exon 1 and included several substitutions and insertion-deletions in the LRR domain. This study provides a basis for further molecular analysis of defense mechanisms against P. brassicae and will contribute to the breeding of resistant cultivars of Brassica vegetables by marker-assisted selection.Data deposition The sequence reported in this paper has been deposited in the GenBank database (accession no. AB605024).